What is the value and impact of quality and safety teams? A scoping review - White, Deborah E; Straus, Sharon E; Stelfox, H T; Holroyd-Leduc, Jayna M; Bell, Chaim M; Jackson, Karen; Norris, Jill M; Flemons, W W; Moffatt, Michael E; Forster, Alan J (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background The purpose of this study was to conduct a scoping review of the literature about the establishment and impact of quality and safety team initiatives in acute care. Methods Studies were identified through electronic searches of Medline, Embase, CINAHL, PsycINFO, ABI Inform, Cochrane databases. Grey literature and bibliographies were also searched. Qualitative or quantitative studies that occurred in acute care, describing how quality and safety teams were established or implemented, the impact of teams, or the barriers and/or facilitators of teams were included. Two reviewers independently extracted data on study design, sample, interventions, and outcomes. Quality assessment of full text articles was done independently by two reviewers. Studies were categorized according to dimensions of quality. Results Of 6,674 articles identified, 99 were included in the study. The heterogeneity of studies and results reported precluded quantitative data analyses. Findings revealed limited information about attributes of successful and unsuccessful team initiatives, barriers and facilitators to team initiatives, unique or combined contribution of selected interventions, or how to effectively establish these teams. Conclusions Not unlike systematic reviews of quality improvement collaboratives, this broad review revealed that while teams reported a number of positive results, there are many methodological issues. This study is unique in utilizing traditional quality assessment and more novel methods of quality assessment and reporting of results (SQUIRE) to appraise studies. Rigorous design, evaluation, and reporting of quality and safety team initiatives are required.